Bed sharing, smoking, and alcohol in the sudden infant death syndrome. New Zealand Cot Death Study Group. Issue 6915 (20th November 1993) - Scragg, R; Mitchell, E A; Taylor, B J; Stewart, A W; Ford, R P; Thompson, J M; Allen, E M; Becroft, D M
Abstract : OBJECTIVES--To investigate why sharing the bed with an infant is a not consistent risk factor for the sudden infant death syndrome in ethnic subgroups in New Zealand and to see if the risk of sudden infant death associated with this practice is related to other factors, particularly maternal smoking and alcohol consumption. DESIGN--Nationwide case-control study. SETTING--Region of New Zealand with 78% of all births during 1987-90. SUBJECTS--Home interviews were completed with parents of 393 (81.0% of total) infants who died from the sudden infant death syndrome in the postneonatal age group, and 1592 (88.4% of total) controls who were a representative sample of all hospital births in the study region. RESULTS--Maternal smoking interacted with infant bed sharing on the risk of sudden infant death. Compared with infants not exposed to either risk factor, the relative risk for infants of mothers who smoked was 3.94 (95% confidence interval 2.47 to 6.27) for bed sharing in the last two weeks and 4.55 (2.63 to 7.88) for bed sharing in the last sleep, after other confounders were controlled for. The results for infants of non-smoking mothers were inconsistent with the relative risk being significantly increased for usual bed sharing in the last two weeks (1.73; 1.11 to 2.70) but not for bed sharing in the last sleep (0.98; 0.44 to 2.18). Neither maternal alcohol consumption nor the thermal resistance of the infant's clothing and bedding interacted with bed sharing to increase the risk of sudden infant death, and alcohol was not a risk factor by itself. CONCLUSION--Infant bed sharing is associated with a significantly raised risk of the sudden infant death syndrome, particularly among infants of mothers who smoke. The interaction between maternal smoking and bed sharing suggests that a mechanism involving passive smoking, rather than the previously proposed mechanisms of overlaying and hyperthermia, increases the risk of sudden infant death from bed sharing.